Urban policies in the framework of the 2030 agenda: Balance and perspectives in Portugal: The Case of Évora - Medeiros, E. (Urban policy in the framework of the 2030 agenda: Balance and perspectives from Latin America and Europe, 2023)
This chapter provides an overview of Portugal's urban policies in the context of the 2030 Agenda, with a particular focus on the country's incorporation of EU policies and strategies. Despite being an EU member state since 1986, Portugal has demonstrated its commitment to the UN's 2030 Agenda, actively contributing to its development through institutional arrangements and participatory approaches. However, the lack of an operative national institutional framework has weakened the multi-institutional dynamic needed for effective implementation. This scenario has also affected Portugal's urban dimension, as there is no national urban agenda. Instead, Portugal's national and regional spatial plans are mostly influenced by EU development visions and urban and regional development strategies, with some alignment to the 11th Sustainable Development Goal (SDG) to make cities inclusive, safe, resilient and sustainable. The Évora SUD, a case study presented in this chapter, highlights Portugal's use of EU-funded policy tools to implement integrated and sustainable urban planning and development approaches. This SUD has contributed to activating territorial collaboration networks, implementing monitoring and evaluation systems and involving citizens and stakeholders in the design and implementation phases. Moreover, it has reinforced intra- and inter-city collaboration processes, leading to a sound and integrated urban development process with the surrounding region. Keywords